Did changes in terrigenous components of deep-sea cherts across the end-Triassic extinction relate to Central Atlantic magmatic province volcanism? - Ikeda, Masayuki; Cho, Tenichi; Bôle, Maximilien (Frontiers in Earth Science, 2023)
The end-Triassic mass extinction event (ETE) is considered to be linked with the emplacement of the Central Atlantic magmatic province (CAMP), yet their temporal relation and underlying nature of global environmental and biotic changes remain controversial. A drastic radiolarian faunal turnover was associated with deep-sea acidification and changes in the chemical composition of pelagic terrigenous components, which were interpreted as the results of increased CAMP-derived material, such as Fe2O3/Al2O3, MgO/Al2O3, and SiO2/Al2O3, without statistical tests. Here we re-examined these CAMP-like signatures in terms of changes in the chemical composition of the Triassic-Jurassic pelagic deep-sea chert succession in Japan. Our newly compiled dataset suggests that changes in Fe2O3/Al2O3 and MgO/Al2O3 across the ETE were not significant, and thus they may not be appropriate proxies for CAMP-derived material potentially due to the dissolution of iron by ocean acidification and the formation of chlorite during the diagenesis, respectively. Decreased SiO2/Al2O3 was also considered to have been reflected in increased CAMP-related dust flux and/or decreased biosiliceous productivity, but a slight increase in Al2O3/TiO2 ratio (a biosiliceous productivity proxy) and an increase in shale bed thickness (dust flux proxy) across the radiolarian ETE implies the increased eolian dust flux rather than decreased productivity. Besides, statistically significant Na-enrichment at the radiolarian ETE level might be related to the CAMP volcanism and/or associated changes in the source areas of eolian dust.